2015
DOI: 10.1016/j.nrleng.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Focal dystonia in musicians: Phenomenology and musical triggering factors

Abstract: Dystonias are defined as a joint sustained and involuntary contraction of agonist and antagonist muscles, which can cause torsion, repetitive abnormal involuntary movements, and/or abnormal postures. One special group of dystonias are those known as occupational, which include dystonia disorders triggered by a repetitive motor activity associated with a specific professional activity or task. Musicians are a population particularly vulnerable to these types of dystonia, which are presented as a loss of coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Data from Latin American countries about MD are scarce, and only isolated reports or small series of cases were found in the English literature. 6 – 10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Latin American countries about MD are scarce, and only isolated reports or small series of cases were found in the English literature. 6 – 10…”
mentioning
confidence: 99%
“…Recently, Aranguiz et al, 6 from Chile, described clinical and demographic characteristics of 12 musicians who developed dystonia. According to the literature, the authors found male predominance (83.3%): eight patients were classical musicians; the hand was the most affected segment (91.7%); and interestingly they described a positive family history of neurological diseases in first-degree relatives in 50% of their patients.…”
mentioning
confidence: 99%